Preoperatory diagnosis of spleen ruture through selective arteriography - Correa, Cosme; Tiscornia, Eduardo (Cirugía del Uruguay, 1977)
Pre-operatory selective arteriography revealed spleen rupture in three patients. An evaluation of clinical, radiological and arteriographic elements in diagnosis of splenic lesion, and the experience with these three cases, indicate that urgency arteriography should be included almost routine procedure, in cases of politraumatized patients.